Pengenalan Media Pembelajaran Matematika Kontekstual Berbasis Lingkungan Sekitar di Suku Baduy - Ismi Widyaningrum; Arina Nur Indriani; Linda Linda; Asep Saefullah Kamali (Indonesia Bergerak : Jurnal Hasil Kegiatan Pengabdian Masyarakat, 2025)
Limited access to learning resources appropriate to the local context presents a challenge in the mathematics learning process in indigenous communities such as the Baduy Tribe. Conventional mathematics learning is often considered too abstract and less relevant to the daily lives of Baduy children, especially in the Outer Baduy region. To address this challenge, this community service activity aims to introduce contextual mathematics learning media based on the surrounding environment and local culture. The media developed is designed to be easily accessible, affordable, and environmentally friendly, while still respecting prevailing traditional values. The method used in this activity is Participatory Action Research (PAR), with a collaborative approach between a team of lecturers and the Outer Baduy community. The activity implementation process includes six stages, namely: identification of local problems and potential, planning, designing learning media, implementation, evaluation, and documentation of activity results. The results of the activity show an increase in interest and understanding of basic mathematics concepts among Outer Baduy children. Children appear more active, enthusiastic, and confident in participating in the learning process through educational games and concrete activities. The media used utilizes natural objects and local cultural elements, such as woodcuts, ancient angklungs, traditional hats, and distinctive Baduy woven motifs. The community responded positively because these media do not conflict with traditional values. This activity has had positive cognitive and social impacts and strengthened awareness of the importance of a contextual and culturally based educational approach as a relevant and inclusive learning strategy.